Assessment of geometrically necessary dislocation levels derived by 3D EBSD. (15th October 2015) - Konijnenberg, P.J.; Zaefferer, S.; Raabe, D.
Graphical abstract: Abstract: Existing alternatives for the calculation of geometrically necessary dislocation (GND) densities from orientation fields are discussed. Importantly, we highlight the role of reference frames and consider different sources of error. A well-controlled micro cantilever bending experiment on a copper bicrystal has been analyzed by 3-dimensional electron back scatter diffraction (3D EBSD). The GND density is determined experimentally by two different approaches and assessed theoretically, assuming a homogeneous bending of the cantilever. Experiment and theory agree very well. It is further shown that the deformation is accommodated mainly by GNDs, which carry and store lattice rotation, and not (only) by mobile dislocations that leave a crystal portion inspected, without lattice rotations. A detailed GND analysis reveals a local density minimum close to the grain boundary and a distinct difference in edge to screw ratios for both grains.